Združevanje poslovnih deležev v družbi z omejeno odgovornostjo - Halvadžić, Belmina (Podjetje in delo, 2023)
This article discusses the merger of shares in a limited liability company. The reasons why certain courts in the past did not (or still do not) allow mergers of business shares and the reasons for the independence of a business shares are discussed. The article presents the foreign legal regime, the documentation required to register the change and a case where it is not rational to oppose such a merger. The conclusions set out the main legal arguments and the conditions to be met for a merger of a business shares.
Keywords: družbe z omejeno dogovornostjo; družbeniki; poslovni delež; pravna ureditev; sodni register